Penggunaan Konsep User Experience Terhadap Layanan Situs Web Perpustakaan - Laylatul Munawaroh (Pustabiblia: Journal of Library and Information Science, 2021)
Building a website should be designed based on the experience of the user, as the user who uses the web service. The basics of user experience are needed in designing a library website. The better the user experience in using a library website, the better the quality of a library's web service will be. Building a library web system requires knowledge of User Experience (UX), so that user satisfaction and convenience can be met. Web-oriented user experience can provide an impressive experience for users with features and content that is not confusing and easy to understand. With the steps in arranging UX into elements, we can better understand the overall task of building a website. According to Jesse James Garett, these elements are divided into five, namely: the strategy plane, the scope plane, the structure plane, the skeleton plane, and the surface plane.